A Novel Mutation in Aicardi–Goutières' Syndrome: A Case Report - Sheikh-Hosseini, Motahareh; Moarefzadeh, Mohammad; Alavi-Moghaddam, Hamideh; Morovvati, Saeid (Journal of Pediatric Neurology, 2020)
Aicardi–Goutières' syndrome (AGS) is a rare heterogeneous genetic disorder characterized by encephalopathy and may bear resemblance to congenital infections. The prevalence of AGS is estimated at more than 4,000 worldwide. Mutations in TREX1 gene are present in ∼22% of patients. We present the case of a 2-year-old boy who came to the Biogene laboratory (Tehran, Iran) with a constellation of congenital disorders but no clear diagnosis. His clinical phenotype consisted of neonatal jaundice, relative microcephaly with diffuse cerebral atrophy in both hemispheres, developmental delay, hypotonia, and nystagmus. There was history of parental consanguineous marriage and prematurity. In our study, a homozygous potentially pathogenic mutation in TREX1 gene associated with AGS1 was detected. This mutation has not been reported in the other patients with AGS. A novel frameshift homozygous potentially pathogenic mutation in TREX1 is postulated to be the cause of disease in our patient.
Keywords: Aicardi–Goutières' syndrome; TREX1 gene; novel mutation